Benefits of Sustained Upregulated Unimolecular GLP-1 and CCK Receptor Signalling in Obesity-Diabetes - Tanday, Neil; English, Andrew; Lafferty, Ryan A.; Flatt, Peter R.; Irwin, Nigel (Frontiers in Endocrinology, 2021)
Combined activation of GLP-1 and CCK1 receptors has potential to synergistically augment the appetite-suppressive and glucose homeostatic actions of the individual parent peptides. In the current study, pancreatic beta-cell benefits of combined GLP-1 and CCK1 receptor upregulation were established, before characterising bioactivity and antidiabetic efficacy of an acylated dual-acting GLP-1/CCK hybrid peptide, namely [Lys12Pal]Ex-4/CCK. Both exendin-4 and CCK exhibited (p<0.001) proliferative and anti-apoptotic effects in BRIN BD11 beta-cells. Proliferative benefits were significantly (p<0.01) augmented by combined peptide treatment when compared to either parent peptide alone. These effects were linked to increases (p<0.001) in GLUT2 and glucokinase beta-cell gene expression, with decreased (p<0.05-p<0.001) expression of NFκB and BAX. [Lys12Pal]Ex-4/CCK exhibited prominent insulinotropic actions in vitro, coupled with beneficial (p<0.001) satiety and glucose homeostatic effects in the mice, with bioactivity evident 24 h after administration. Following once daily injection of [Lys12Pal]Ex-4/CCK for 28 days in diabetic high fat fed (HFF) mice with streptozotocin (STZ)-induced compromised beta-cells, there were clear reductions (p<0.05-p<0.001) in energy intake and body weight. Circulating glucose was returned to lean control concentrations, with associated increases (p<0.001) in plasma and pancreatic insulin levels. Glucose tolerance and insulin secretory responsiveness were significantly (p<0.05-p<0.001) improved by hybrid peptide therapy. In keeping with this, evaluation of pancreatic histology revealed restoration of normal islet alpha- to beta-cell ratios and reduction (p<0.01) in centralised islet glucagon staining. Improvements in pancreatic islet morphology were associated with increased (p<0.05) proliferation and reduced (p<0.001) apoptosis of beta-cells. Together, these data highlight the effectiveness of sustained dual GLP-1 and CCK1 receptor activation by [Lys12Pal]Ex-4/CCK for the treatment of obesity-related diabetes.